Missing observations: The loss in relative A-, D- and G-efficiency - Iwundu, Mary (International Journal of Advanced Mathematical Sciences, 2017)
The loss in Relative A-, D- and G-efficiency due to missing single or multiple observations is studied using cuboidal designs associated with response models. Higher losses in Relative A- and D-efficiencies are attributed to missing vertex points. The absence of one or two center points does not affect any of Relative A-, D- and G-efficiency, but when its absence is in combination with either a vertex or axial point, there is some negative effect on the design efficiency resulting in some percentage loss in Relative efficiency. The loss in relative efficiency is higher when the missing center point is in combination with missing vertex point. Losses in Relative A- and D-efficiencies are generally higher than losses in Relative G-efficiency. In fact, Relative G-efficiency is mildly affected by the missing vertex or axial point or both.